Bone Mineralization Changes in the Subchondral Bone of the Medial Gutter in Chronic Lateral Ankle Instability. (November 2020) - Nakasa, Tomoyuki; Ikuta, Yasunari; Ota, Yuki; Kanemitsu, Munekazu; Sumii, Junichi; Nekomoto, Akinori; Adachi, Nobuo
Background: Chronic ankle instability (CAI) induces osteoarthritis (OA) by inflicting abnormal stresses on the medial gutter. It is important to detect early OA change and to explore factors likely to induce the OA. The purpose of this study was to evaluate subchondral bone change in the medial gutter of CAI using computed tomography (CT) scans. Methods: Thirty-five ankles with CAI (CAI group) and 35 ankles without CAI (control group) were included. The region of interest (ROI) in the subchondral bone of the medial gutter on CT axial images was set on the tibia and talus. The Hounsfield unit (HU) in ROIs was measured and corrected by the HU of the fibula in the same slice. HU ratios were compared between the CAI and control groups. In the CAI group, the relationship between the HU ratio and the talar tilt angle (TTA), OA change, and the anterior talofibular ligament (ATFL) remnant quality were analyzed. Results: The mean HU ratio in the CAI group was significantly higher than that in the control. In the CAI group, HU ratios in ≥10 degrees of TTA were significantly higher than those in <10 degrees. But there was no significant difference in the HU ratios with or without OA change in the medial gutter. A good-quality ATFL remnant showed a low HU ratio compared with that with poor quality. Conclusion: CAI patients exhibited subchondral bone change in the medial gutter, which suggests that the elimination of instability may help to prevent or decrease the development and/or progression of osteoarthritis. Level of Evidence: Level III, comparative series.